A local view on the Hudetz correction of the Yager entropy of dynamical systems. Issue 3 (3rd April 2019) - Rahimi, Mehdi; Mohammadi Anjedani, Mohammad
ABSTRACT: In this paper, we define a local version of Hudetz correction for the Yager entropy of dynamical systems. It is proved that the introduced function is indeed a local entropy map for the Hudetz correction of the Yager entropy, in the sense that, the Hudetz correction of the Yager entropy of a continuous map on a compact metric space is attained by integrating the introduced local entropy.